1975
DOI: 10.2136/sssaj1975.03615995003900010013x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stones on the Hydraulic Conductivity of Relatively Dry Desert Soils

Abstract: The objective of this study was to determine whether moisture transmission properties of stony soils could be evaluated using samples of the same soil in which the stony fraction (> 2 mm) had been excluded. Experiments were conducted in the laboratory on soil columns with and without stones. Unsaturated hydraulic conductivity (K) was measured with a transient outflow method over the matric potential range of −0.05 to −50 bars using tensiometers and soil psychrometers. The soils studied were Rock Valley grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 0 publications
1
32
2
1
Order By: Relevance
“…Mehuys et al (1975) experimented with stony desert soils (up to 40% by mass of gravels with particle diameter >2 mm) and found that the presence of stones had no appreciable effect on the relationship between unsaturated hydraulic conductivity, K, and pressure head of soil water, ψ. Infiltration in stony soils decreases with increasing rock content because of the less accessible surface for water flow (Valentin 1994). Furthermore, the more spherical rock fragments are, the lower the saturated hydraulic conductivity (Dunn and Mehuys 1984).…”
Section: Gravel Effects On Hydraulic Conductivitymentioning
confidence: 99%
“…Mehuys et al (1975) experimented with stony desert soils (up to 40% by mass of gravels with particle diameter >2 mm) and found that the presence of stones had no appreciable effect on the relationship between unsaturated hydraulic conductivity, K, and pressure head of soil water, ψ. Infiltration in stony soils decreases with increasing rock content because of the less accessible surface for water flow (Valentin 1994). Furthermore, the more spherical rock fragments are, the lower the saturated hydraulic conductivity (Dunn and Mehuys 1984).…”
Section: Gravel Effects On Hydraulic Conductivitymentioning
confidence: 99%
“…All of these methods are time and energy consuming and difficult to obtain satisfactory results in a heterogeneous medium. In addition, although the impact of size, content and distribution of rock fragments on soil water movement have been studied by many scholars, conflicting trends often exist in various reports revealing positive correlations, negative correlations, no correlations or a "turning point" between the size/content and infiltration ability (conduction) (Mehuys et al 1975;Bouwer and Rice 1984;Ravina and Magier 1984;Brakensiek et al 1986;Sauer and Logsdon 2002;Khaleel and Heller 2003). Consequently, it has been a challenge to understand the impact of rock fragments on soil hydraulic character, especially at a heterogeneous research site.…”
Section: Introductionmentioning
confidence: 99%
“…However, extensive data sets on unsaturated K and its variability are generally not available because of the significant time and effort involved in obtaining accurate measurements, especially in the dry range [e.g., Khaleel et al, 1995]. The problem is further complicated by the frequent presence of a high gravel fraction in vadose zone soils in an arid setting [Mehuys et al, 1975;Russo, 1983b;Bouwer and Rice, 1984;Khaleel and Relyea, 1997].…”
Section: Introductionmentioning
confidence: 99%